Fluorescence Cross-Correlation Spectroscopy Yields True Affinity and Binding Kinetics of Plasmodium Lactate Transport Inhibitors - Iga Jakobowska; Frank Becker; Stefano Minguzzi; Kerrin Hansen; Björn Henke; Nathan Hugo Epalle; Eric Beitz; Stefan Hannus (MDPI AG, 2021)
Blocking lactate export in the parasitic protozoan Plasmodium falciparum is a novel strategy to combat malaria. We discovered small drug-like molecules that inhibit the sole plasmodial lactate transporter, PfFNT, and kill parasites in culture. The pentafluoro-3-hydroxy-pent-2-en-1-one BH296 blocks PfFNT with nanomolar efficiency but an in vitro selected PfFNT G107S mutation confers resistance against the drug. We circumvented the mutation by introducing a nitrogen atom as a hydrogen bond acceptor site into the aromatic ring of the inhibitor yielding BH267.meta. The current PfFNT inhibitor efficiency values were derived from yeast-based lactate transport assays, yet direct affinity and binding kinetics data are missing. Here, we expressed PfFNT fused with a green fluorescent protein in human embryonic kidney cells and generated fluorescent derivatives of the inhibitors, BH296 and BH267.meta. Using confocal imaging, we confirmed the location of the proposed binding site at the cytosolic transporter entry site. We then carried out fluorescence cross-correlation spectroscopy measurements to assign true Ki-values, as well as kon and koff rate constants for inhibitor binding to PfFNT wildtype and the G107S mutant. BH296 and BH267.meta gave similar rate constants for binding to PfFNT wildtype. BH296 was inactive on PfFNT G107S, whereas BH267.meta bound the mutant protein albeit with weaker affinity than to PfFNT wildtype. Eventually, using a set of PfFNT inhibitor compounds, we found a robust correlation of the results from the biophysical FCCS binding assay to inhibition data of the functional transport assay.